Switching from a gonadotropin-releasing hormone (GnRH) agonist to a GnRH antagonist in prostate cancer patients: A systematic review and meta-analysis - S. Atchia, Kaleem; Wallis, Christopher J.D.; Fleshner, Neil; Toren, Paul (Canadian Urological Association Journal, 2019)
Introduction: We sought to address whether there are clinical responses when patients who are failing gonadotropin-releasing hormone (GnRH) agonist therapy are switched to degarelix. Androgen-deprivation therapy remains the backbone of treatment for disseminated prostate cancer and may be achieved with orchiectomy, GnRH agonists, or degarelix, a GnRH antagonist. Methods: We conducted a systematic review and meta-analysis with a search of the BIOSIS Previews, Embase, International Pharmaceutical Abstracts, MEDLINE, and Google Scholar databases using key terms. Quantitative meta-analysis was performed to provide a pooled estimate of prostate-specific antigen (PSA) response at three months. Results: Thirteen studies were identified, eight of which were included in the qualitative and quantitative analyses. Patient characteristics were broadly similar between the studies. Out of 155 patients across all included studies, 20 had stable PSA after the switch (12.9%), 14 had a 10‒30% decrease in PSA (9.0%), three had a 30‒50% decrease (1.9%), and 13 had a more than 50% decrease (8.4%). Random effects meta-analysis of these data demonstrated a pooled response rate of 27.75% (95% confidence interval 18.9‒36.5%; I2=7.9%). Changes in testosterone levels following the switch could not be quantitatively assessed due to lack of sufficient data. Conclusions: Our results suggest that a switch to GnRH antagonist following progression on a GnRH agonist may result in a stable or decreased PSA at three months in about 30% of patients. This information should be considered among the potential options to discuss with patients with a rising PSA on GnRH agonist therapy.